Penataan Sistem Pemilihan Umum yang Berkeadilan untuk Penguatan Sistem Presidensiil Di Indonesia - Mohammad Syaiful Aris (Universitas Airlangga, 2018)
Justice in election one of the constitutional mandates expressly in Article 22E Paragraph (1) of the 1945 Constitution of the State of the Republic of Indonesia. Nevertheless the Constitution does not provide further guidance on what the meaning of justice in election. Therefore, it is necessary to search philosophically what exactly the meaning of justice in the election. An alternative system is needed as a bridge between the proportional system and the district system. An alternative system must be able to create a minimum majority party in parliament to support presidential policies, improve the accountability the member of parlements and accommodate heterogeneous groups.